Studi Kasus Pola Komunikasi dalam Meningkatkan Kinerja pada Dinas Komunikasi dan Informatika Provisi Sumatera Selatan - Mahendra, Yusril Ihza; Maharani, Dwi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
This research aims to determine organizational communication patterns in the departmen tcommunication and informatics in the city of Palembang. Humans as social creatures need communication in their lives, meaning they need other people or groups to interact with each other. The method used is qualitative research. Then the research object is in the communication and information service of the city of Palembang, Sumatra, while the research subject is the head of the e-government services sector, head of the application development section, technical personnel. The results of this research are agencies under the auspices of the Palembang city government which carries out the authority for communication and government affairs. informatics